Kedudukan Anak Hasil Waṭ‘u al-Syubhat dan Implikasinya dalam Hukum Islam - Muhammad Yusram; Abdul Munawir; Afandi Winata K. Dayani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out the position and implications of children resulting from waṭ’u al-syubhat in Islam. This research is library research with a qualitative type of research and uses a normative and normative juridical approach. The results of the research obtained are as follows: first, marriage is a contract that makes it halal for men and women to perform jimak, with certain harmony and conditions that are taught in the Al-Qur'an and hadith. Second, waṭ’u al-syubhat is jimak which is haram but is carried out because of one or several mistakes due to ignorance or unawareness, so that the perpetrator is not punished as for zina. There is a type of waṭ’u al-syubhat which occurs because the marriage contract is fa>sid (broken), there is also a type of waṭ’u al-syubhat which occurs due to ignorance or unconsciousness so that he has sexual intercourse with a woman who is haram for him to have sexual intercourse with. Third, children resulting from waṭ’u al-syubhat still have their rights as children like children born in a legal marriage, including birth rights, livelihood, guardianship and inheritance. If this waṭ’u al-syubhat occurs in a marriage whose contract is fa>sid (broken), then the child born still gets his rights from his two syubhat parents. If this waṭ’u al-syubhat occurs during sexual intercourse caused by unconsciousness or ignorance, then the child born from waṭ’u al-syubhat will get all his rights from his parents. both and it could also be one of them.